2016
DOI: 10.1111/nyas.13093
|View full text |Cite
|
Sign up to set email alerts
|

Clearing the haze: the complexities and challenges of research on state marijuana laws

Abstract: As states increasingly liberalize marijuana laws, high-quality research is needed that will inform the public and policymakers about the health and societal impact of these laws. However, there are many challenges to studying marijuana policy, including the heterogeneity of the drug and its use, the variability in the laws and their implementation from state to state, the need to capture a wide variety of relevant outcomes, and the poorly understood influence of marijuana commercialization. Furthermore, curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 95 publications
(176 reference statements)
0
26
0
Order By: Relevance
“…For example, some studies have demonstrated that having or passing an LCL is related to greater prevalence of cannabis use in a state (Cerda, Wall, Keyes, Galea, & Hasin, 2012; Schuermeyer, et al, 2014; Stolzenberg, D’Alessio, & Dariano, 2016; Wen, Hockenberry, & Cummings, 2015) while other studies have demonstrated no effect (Harper, Strumpf, & Kaufman, 2012; Lynne-Landsman, Livingston, & Wagenaar, 2013). The lack of consistent findings may be due in part to the use of dichotomous variables representing the presence or absence of an LCL (Choo & Emery, 2017; Hunt & Miles, 2015; Pacula, Powell, Heaton, & Sevigny, 2015). No two LCL are exactly the same and analytical strategies that rely on yes/no LCL comparisons may obfuscate important underlying policy heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have demonstrated that having or passing an LCL is related to greater prevalence of cannabis use in a state (Cerda, Wall, Keyes, Galea, & Hasin, 2012; Schuermeyer, et al, 2014; Stolzenberg, D’Alessio, & Dariano, 2016; Wen, Hockenberry, & Cummings, 2015) while other studies have demonstrated no effect (Harper, Strumpf, & Kaufman, 2012; Lynne-Landsman, Livingston, & Wagenaar, 2013). The lack of consistent findings may be due in part to the use of dichotomous variables representing the presence or absence of an LCL (Choo & Emery, 2017; Hunt & Miles, 2015; Pacula, Powell, Heaton, & Sevigny, 2015). No two LCL are exactly the same and analytical strategies that rely on yes/no LCL comparisons may obfuscate important underlying policy heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…However, as was shown in some of the reviewed evidence (e.g. [57]), and discussed in greater detail elsewhere [100][101][102], the passage of a law to legalise cannabis use does not necessarily indicate an open cannabis market. Studies that measure access to cannabis through other means (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Relationships between cannabis use and the use of alcohol, tobacco and opioids will substantially affect the public health impacts of cannabis legalization 38,40,42 . The public health burdens of these drugs could be reduced if cannabis becomes a substitute, while their impact could be amplified if there is more concurrent use of cannabis and these drugs 38,40 .…”
Section: What Adverse Health Effects May Increase After Cannabis Legamentioning
confidence: 99%
“…It has taken time to produce dependable supplies of cannabis within states that have legalized, and there are a limited number of retail outlets available in a relatively small number of locations in these states 1 . For these reasons, evaluations of the first five or so years after legalization may provide a poor indication of the impacts of cannabis use on public health when the industry develops over a decade or more 42,77 .…”
Section: Health Effects Of Legalizing Recreational Cannabis Use In Thmentioning
confidence: 99%
See 1 more Smart Citation